2013
DOI: 10.1097/qad.0b013e32835cfc82
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-specific intercellular adhesion molecule-3 grabbing nonintegrin mediates HIV-1 infection of and transmission by M2a-polarized macrophages in vitro

Abstract: Objective To assess in-vitro effects of monocyte-derived macrophage (MDM) polarization into M1 and M2a cells on HIV-1 replication and transmission and obtain new insights into the potential importance of macrophage polarization in vivo. Design Human peripheral blood monocytes were differentiated into MDM for 7 days. Control and MDM polarized into M1 or M2a cells were exposed to different strains of HIV-1 and assessed for their ability to bind and transmit virus to CD4+ T lymphocytes. Methods MDM were incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…IL-13 also promotes differentiation of B cells into Ab-secreting plasma cells. M2 macrophages express more DC-SIGN than M1 macrophages (Cassol et al, 2012), supporting the concept that M2 macrophages are likely to serve as a more efficient target cell for HHV-8 infection. Importantly, multiple receptors are needed for efficient infection of these macrophages by HHV-8.…”
Section: Hhv-8 Infection Of Professional Apcmentioning
confidence: 76%
“…IL-13 also promotes differentiation of B cells into Ab-secreting plasma cells. M2 macrophages express more DC-SIGN than M1 macrophages (Cassol et al, 2012), supporting the concept that M2 macrophages are likely to serve as a more efficient target cell for HHV-8 infection. Importantly, multiple receptors are needed for efficient infection of these macrophages by HHV-8.…”
Section: Hhv-8 Infection Of Professional Apcmentioning
confidence: 76%
“…In the nodes, mDC activate the specific CD4 + T cells that become infected by a “kiss of death” delivered by the DC-SIGN associated virus. DC-SIGN expression has been later described in other cells such as macrophages 8, 9 where it likely plays a similar role 9. Other molecules, such as CD206/mannose receptor have been also credited with similar functions in the context of HIV infection 10.…”
Section: Hiv Entry Into Cd4+ Cells Of the Immune Systemmentioning
confidence: 99%
“…14,15,40 Recently, we have reported that expression of dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin is present and enhanced in unpolarized and M2a-MDM, respectively, whereas it downregulates M1-cells, 21 therefore representing a potentially useful marker to distinguish between M1-and M2-macrophages in vivo. Dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin expression by M2a-MDM, on the one hand, may compensate for the decreased levels of CD4 on the surface of these cells, but, on the other hand, facilitate virion transmission to CD4 + T cells, in analogy to its already demonstrated role in dendritic cell.…”
Section: Macrophage Polarization and Hiv-1 Infectionmentioning
confidence: 99%